Similarities and Differences: A Comparative Review of the Molecular Mechanisms and Effectors of NAFLD and AFLD - Zhang, Pengyi; Wang, Weiya; Mao, Min; Gao, Ruolin; Shi, Wenting; Li, Dongmei; Calderone, Richard; Sui, Bo; Tian, Xuewen; Meng, Xiangjing (Frontiers in Physiology, 2021)
Non-alcoholic fatty liver disease (NAFLD) and alcoholic fatty liver disease (AFLD) are the most prevalent metabolic liver diseases globally. Due to the complex pathogenic mechanisms of NAFLD and AFLD, no specific drugs were approved at present. Lipid accumulation, oxidative stress, insulin resistance, inflammation, and dietary habits are all closely related to the pathogenesis of NAFLD and AFLD. However, the mechanism that promotes disease progression has not been fully elucidated. Meanwhile, the gut microbiota and their metabolites also play an important role in the pathogenesis and development of NAFLD and AFLD. This article comparatively reviewed the shared and specific signaling pathways, clinical trials, and potential intervention effectors of NAFLD and AFLD, revealing their similarities and differences. By comparing the shared and specific molecular regulatory mechanisms, this paper provides mutual reference strategies for preventing and treating NAFLD, AFLD, and related metabolic diseases. Furthermore, it provides enlightenment for discovering novel therapies of safe and effective drugs targeting the metabolic liver disease.